A Computational Perspective of the Competitive Decomposition and Isomerization of $CH_3OCHFO$ Radical (Journal of Atomic and Molecular Sciences, 2013)
A detailed quantum chemical study is performed on the mechanism of the $CH_3OCHFO$ radical formed during the photooxidation of $CH_3OCH_2F (HFE-161),$ including the main decomposition and isomerization processes at the G2(MP2)//MPWB1K level of theory. The results clearly point out that the $β-C-H$ bond scission is the dominant path involving the lowest energy barrier of 8.16 kcal $mol^{-1}$ calculated at G2(MP2) level of theory. On the basis of the results obtained during the present investigation, the thermal rate constant for the different reaction channels involved during the isomerization and decomposition processes of $CH_3OCHFO$ are evaluated at 298 $K$ and 1 atm using Canonical Transition State Theory. The results are compared with the data available in the literature.
Keywords: theoretical study; hydrofluoroethers; G2 method; isomerization; canonical transition state theory.